The Song of Songs through the ages: essays on the Song's reception history in different times, contexts, and genres - Schellenberg-Lagler, Annette (Studies of the Bible and its reception, 2023)
Intro -- Contents -- The Song of Songs Through the Ages -- Between Hippolytus and Athanasius: The Variety of Patristic Song of Songs' Interpretations -- "Dripping from the Lips of Sleeping Ones": The Interpretation of the Song of Songs from Tannaitic Literature to the Palestinian Talmud -- The Exegesis of all Exegeses: The Uniqueness of Shir HaShirim Rabbah's Approach to the Song of Songs -- "I Slept but My Heart Was Awake": Rabbinic Interpretations of Song of Songs 5:2 -- Reading the Old English Life of Saint Mary of Egypt with Abbot Hadrian of Africa: The Influence of Byzantine Readings of the Song of Songs on Early Medieval England -- Targum Song of Songs, the History of Israel, and the Study of Torah -- Do Not Wake or Arouse Love: Erotics of Time and the Dream of Messianic Waiting -- Of Songs and Sequels: The Song of Songs in the Hebrew Liturgical Poetry of Al-Andalus -- A Vocabulary of Love: The Song of Songs in the Secular Hebrew Love Poetry from Muslim Spain -- Bernard of Clairvaux: The Song of Songs as an Instruction on the Spiritual Life -- Preaching the Song of Songs at Admont: A Minority Report from the Twelfth Century -- Voices Shifting and Voices Layered: The Song of Songs in Medieval German Commentaries -- An Ecology of Desire: Pierre d'Ailly's First Theological Work, a Latin Commentary on the Song of Songs -- Lovers, Gardens, and Wounds: An Exploration of the Medieval Iconographies of the Song of Songs -- Singing the Song of Songs in the Late Middle Ages and the Renaissance: The Evidence of the Alamire Manuscripts -- Early Modern Women Comment on the Song of Songs -- Varieties of Reformed and Puritan Reception of the Song of Songs, 1550-1730 -- The Song of Songs in Late Eighteenth-Century Germany: Theology and Desire -- The Song of Songs as a Drama: A Radical Change of Interpretation in the Eighteenth and Nineteenth Century.